1994
DOI: 10.1103/physrevb.49.17011
|View full text |Cite
|
Sign up to set email alerts
|

Electron paramagnetic resonance related to optical charge-transfer processes in ZnSe:Ti

Abstract: In ZnSe crystals grown by different techniques, titanium ions are incorporated as Ti +(d ) andTi +(d') centers on Zn sites. A strong Jahn-Teller (JT) effect acts on the doubly degenerate E ground state of Ti3+. The electron paramagnetic resonance (EPR) at T =3 K indicates a quasistatic JT effect of the ground state and a quasidynamic one of the first excited state for the strain-split vibronic E-A2 manifold. These effects are distinguished by their angular variations and the g values. Ti + causes an isotropic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 19 publications
1
8
0
1
Order By: Relevance
“…10 This is remarkable insofar as our recent experiments on V impurities in ZnS and ZnSe point towards an interplay of these more complicated possibilities.…”
Section: Discussionmentioning
confidence: 94%
“…10 This is remarkable insofar as our recent experiments on V impurities in ZnS and ZnSe point towards an interplay of these more complicated possibilities.…”
Section: Discussionmentioning
confidence: 94%
“…We have not herein, or previously (1), considered JahnTeller distortions which, by reference to other d 1 ions in zircon (20,21) and Ti 3ϩ ions in other crystals (22), are presumably present. It was found that there are apparently no features in the present study which required such an analysis.…”
Section: A the Electronic Zeeman And Nuclear Hyperfine Interactionsmentioning
confidence: 89%
“…The optical absorption and EPR spectra of V 3+ and Ti 2+ in tetrahedral crystals have been reported [21][22][23][24]. Their results indicate that these TMIs usually occupy sites of cubic symmetry.…”
Section: Calculation and Analysismentioning
confidence: 91%
“…V 3+ and Ti 2+ , which are usually regarded as the typical ions with d 2 configuration, have been extensively studied by many physicists and chemists [18][19][20][21][22][23][24][25][26][27][28][29]. The optical absorption and EPR spectra of V 3+ and Ti 2+ in tetrahedral crystals have been reported [21][22][23][24].…”
Section: Calculation and Analysismentioning
confidence: 98%